Di-(2-Ethylhexyl) Phthalate Increases Obesity-Induced Damage to the Male Reproductive System in Mice. (17th May 2018) - Zhao, Jian; Ren, Shi; Liu, Chunyu; Huo, Li; Liu, Zheng; Zhai, Lingling
Abstract : Objective . This study evaluated the effects of di-(2-ethylhexyl) phthalate (DEHP) and obesity on male reproductive organ function in male mice and the potential mechanism of male secondary hypogonadism (SH) in such mice. Methods. 140 mice were assigned to six groups for 12 weeks: normal, DEHP, DIO, DIO + DEHP low, DIO + DEHP middle, and DIO + DEHP high. The effects of DEHP and obesity upon the reproductive organs were determined by measuring sperm count and motility, relative testis and epididymis weight, hormone level, and pathological changes. Oxidative stress was evaluated by determining malondialdehyde, T-AOC, SOD, GSH, H2 O2, CAT, and GSH-PX in testicular tissues. Nrf2 and Keap1 protein were measured by Western blotting. Results. DEHP and obesity reduced sperm count and motility, relative testis and epididymis weight, and testosterone level but increased the levels of MDA, H2 O2, leptin, and estradiol. Pathological injury was observed in the testicular Leydig cells. Moreover, the activity of CAT, SOD, and GSH-Px enzymes was inhibited. Nrf2 protein expression was reduced but that of Keap1 was increased. Conclusions. DEHP and obesity jointly caused damage to male productive function. Oxidative stress in testicular tissue, and a high level of leptin, may provide some evidence to clarify the mechanisms of male SH with DEHP and obesity.